A survey of micrometeorological parameters within a forest canopy at Fort Polk, Louisiana - Cionco, Ronald M., author; Sadeh, Willy Z., author; Law, Francis W., author; Marlatt, William E., author; Fox, Douglas G., author; Dietrich, David L., author; U.S. Army Electronics Research and Development Command, Atmospheric Sciences Laboratory, publisher (Colorado State University. Libraries, 1982)
A field investigation of micrometeorological parameters inside and above a forest canopy at Fort Polk, Louisiana, was conducted in conjunction with the Atmospheric Sciences Laboratory Dusty Infrared Test IIIA. The three orthogonal components of the wind, ory- and wet-bulb temperatures and total solar radiation were measured inside this forest canopy by means of an instrumented meteorological tower. In addition, turbulence inside the forest canopy was monitored by means of hot-wire anemometers. Tethersonde balloon sounding above the forest canopy was further performed. The meteorological data was reduced by means of three different statistical methods. Single sample period values, one-minute sample averages and sequential sample values were computed. The latter two methods led to the construction of time series which can readily be used to perform advanced statistical analyses. Totals of 27 h 29 min of meteorological tower data and 2 h 50 min of balloon data were reduced. The results are presented in tabular form in 1422 tables and partially displayed in 1795 figures under separate cover in view of their large volume. Selected samples of the results are, however, presented herein. The results supply a data base for analyses of airflow in a forest canopy. Suggestions for future work of significance for mission-oriented cases and for modeling of airflow in a forest canopy are outlined.
CER80-81WZS-FWL-WEM44.
February 1982.
Keywords: Forest meteorology -- Louisiana; Micrometeorology -- Louisiana